State of Charge Estimation for Lithium-Ion Batteries Using Model-Based and Data-Driven Methods: A Review - How D.N.T.; Hannan M.A.; Hossain Lipu M.S.; Ker P.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Classification (of information); Disaster prevention; Electric discharges; Electric vehicles; Estimation; Ions; Life cycle; Lithium-ion batteries; Data-driven approach; Data-driven methods; High energy densities; Mathematical equations; Model based approach; Model-based method; State of charge; State-of-charge estimation; Battery management systems